Analisis Penggunaan Gaya Bahasa dalam Menyoroti Perspektif Feminisme dalam Novel Hati Suhita - Siregar, Namira Az Zahra (Jurnal Bahasa dan Sastra, 2024)
This research has an urgency to explore the use of language styles by raising the perspective of feminism in the novel Hati Suhita by Khilma Anis. Hati Suhita is a contemporary Indonesian literary work that not only tells the story of women's lives within the framework of culture and religion, but also highlights feminist issues that are relevant to the modern social context. This research aims to explore the messages of feminism through language styles in the novel. In this novel, Khilma Anis uses various stylistic elements such as metaphor, simile, irony, and symbolism to strengthen her feminist narrative. This study uses the textual analysis method to identify and analyze the use of these elements and how they function in conveying feminist messages. The results of the analysis show that the use of metaphor and symbolism in Hati Suhita can help deepen readers' understanding of women's struggle against patriarchy and restrictive social norms. For example, the use of metaphors related to nature and spiritual elements illustrate the complexity of women's emotions and inner strength. In addition, irony is often used to criticize gender injustice and unfair social expectations of women. Similes are used to draw strong comparisons between the conditions of women in the novel and the situations women face in real life.